The Walking Interview: A Promising Method for Promoting the Participation of Autistic People in Research Projects. (8th April 2022) - Marcotte, Justine; Grandisson, Marie; Milot, Élise; Dupéré, Sophie
Walking interviews are increasingly used in the field of health to understand the relationship between individuals and places. With this method, the interviewer and the participant move from place to place within an environment and use it to enrich the discussion. Several advantages have been reported concerning its use, such as the richness of the data it provides and that it allows interviewers to immerse themselves in the participant's world. This article is based on the experience of using walking interviews in an innovative context, with 10 autistic adolescents and adults and 13 parents. The method was used in the participants' home environment, as part of study conducted in Québec (Canada) on home environment factors that influence autistic people's independence at home. It was chosen to meet the study objectives, but also to support the participation of autistic people in research interviews. These people's participation in research can be a challenge when data collection methods are not adapted, given the difficulties that some have communicating and interacting socially, as well as discussing abstract topics. In this article, the advantages, limitations and suggestions related to the use of walking interviews are reported from the participants' and interviewer's perspectives. The authors also discuss the potential for using walking interviews to collect the perspectives of other populations, especially those with difficulties expressing themselves, such as allophones or people with language disorders.